Spin control : the White House Office of Communications and the management of presidential news - Maltese, John Anthony (Chapel Hill ; London : The University of North Carolina Press, 1994)
Spin Control, originally published in 1992, chronicles the development of the powerful White House Office of Communications and its pivotal role in molding our perception of the modern presidency. In this new edition, John Maltese brings his analysis up to date with a chapter detailing the media techniques of the Bush administration, the 1992 presidential campaign (including the use of talk shows like 'Larry King Live'), and the early Clinton administration.
Acknowledgments -- Introduction -- Origins of the Office of Communications -- The Nixon years: beginnings and evolution -- The Nixon years: a house divided -- The Ford years: decline and resurgence -- The Carter years: getting control -- The Reagan years: perfecting the art of communication -- The Bush and Clinton years: postscript -- Appendix -- Notes -- Bibliography -- Index.
Includes bibliographical references (pages 289-303) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Online resource (HeinOnline, viewed June 2, 2020).
Keywords: USA -- White House Communications Office; Presidents -- United States -- Press conferences; Government and the press -- United States; État et presse -- États-Unis.; POLITICAL SCIENCE -- Public Affairs & Administration; Presidents; Government and the press; Presidents -- Press conferences; United States; Geschichte; Beeldvorming; Berichtgeving; Presidentschap; Office of Communications; Press conferences